Menciptakan Suasana Belajar Yang Menyenangkan Pada Pembelajaran Matematika Disekolah Integrasi - Saparudin Saparudin; Irda Junita; Muhammad Pazuli; Opi Andriani (BADAN PENERBIT STIEPARI PRESS, 2024)
Education plays an important role in preparing quality human resources capable of being competent in the development of science and technology, so education must be implemented as well as possible to obtain maximum results. Learning mathematics can help and train children with special needs in communicating and interacting with society. Apart from that, studying mathematics can train the brain to think logically and can develop children's creativity. Children who can develop their creativity will be well accepted by society.